2012
DOI: 10.5792/ksrr.2012.24.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Posterior Cruciate Ganglion Cyst Causing Impingement between Posterior Root of the Medial Meniscus and Anterior to the Posterior Cruciate Ligament

Abstract: There are several reports of symptomatic ganglion cysts near the posterior cruciate ligament (PCL), but no reports of a symptomatic ganglion originating from the anterior aspect of the PCL in the deep recess between the posterior root of the medial meniscus and the PCL, bulging into the posteromedial joint space. In this report, we present the clinical features of a patient with a symptomatic ganglion cyst treated successfully by arthroscopic excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Literatures showed that the changes in the length and torsion of PCL induced by knee flexion might cause traction or compression on cysts, which may stimulate the nerve endings on synovium and result in limited ROM secondary to pain and abnormal sensation [ 1 , 2 , 12 , 13 ]. Previous studies reported that the clinical manifestations of symptomatic PCL cyst might include arthralgia, joint swelling and effusion, and restricted ROM induced by pain [ 1 4 , 6 8 , 12 , 14 17 ]. Our results are similar to the above reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literatures showed that the changes in the length and torsion of PCL induced by knee flexion might cause traction or compression on cysts, which may stimulate the nerve endings on synovium and result in limited ROM secondary to pain and abnormal sensation [ 1 , 2 , 12 , 13 ]. Previous studies reported that the clinical manifestations of symptomatic PCL cyst might include arthralgia, joint swelling and effusion, and restricted ROM induced by pain [ 1 4 , 6 8 , 12 , 14 17 ]. Our results are similar to the above reports.…”
Section: Discussionmentioning
confidence: 99%
“…The lesion is commonly seen in people aged 20–40 years old and involves more males than females [ 1 3 ]. Compared with anterior cruciate ligament (ACL) cyst, posterior cruciate ligament (PCL) cyst is relatively seldom seen [ 3 , 4 ]. Since not all PCL cysts are symptomatic, the reports of PCL cysts were hardly found until the wide utilization of MRI and arthroscopy two decades ago [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ganglion cysts (GC) arising from the cruciate ligaments are rare, with a reported prevalence of 0.36% when detected by MRI and 0.8% by knee arthroscopy [ 2 ]. Posterior cruciate ligament (PCL) ganglion cysts occur less frequently than those arising from the anterior cruciate ligament (ACL) [ 3 , 4 ]. Krudwig et al, in a study conducted on over 8000 knee arthroscopies in a 15-year period, reported a prevalence of ganglion cysts originating from the ACL more than three times higher than the PCL ones [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Not all PCL cysts are symptomatic; however, in a few cases, they may be clinically relevant, causing knee pain and limiting flexion. [1][2][3] Most PCL cysts are found fortuitously by ultrasound, magnetic resonance imaging (MRI), or arthroscopy performed for other pathologies of the knee. [3][4][5][6][7] Initial treatment with medication and corticosteroid injections resolves most cases.…”
mentioning
confidence: 99%